GAMBARAN STATUS RESISTENSI RIFAMPISIN PASIEN TUBERKULOSIS EKSTRA PARU (TBEP) PEMERIKSAAN TES CEPAT MOLEKULER (TCM) DI RSUD CILACAP PERIODE JANUARI – OKTOBER 2025 - Legiana Elza Syariah; Fitri Galih Ramadhani; Junior Dwi Cahyo; Meka Faizal Farabi; Dwi Sulistyowati; Fery Nugroho (LPPM Universitas Abdurrab, 2026)
Extrapulmonary tuberculosis (EPTB) is tuberculosis that occurs outside the respiratory system and often experiences delays in diagnosis due to the characteristics of low-concentration specimens. The Xpert MTB/RIF-based Molecular Rapid Test (TCM) is recommended as an initial diagnostic method because it can detect Mycobacterium tuberculosis and rifampicin resistance quickly. This study aims to describe the results of TCM examination and rifampicin resistance status in EPTB cases at Cilacap Regional Hospital during January–October 2025. This study used a non-experimental observational design with a retrospective descriptive approach. Data were obtained from TCM examination results on extrapulmonary specimens of EPTB patients. The results showed that of all EPTB samples examined, a small proportion were detected positive for Mycobacterium tuberculosis. The majority of positive samples showed sensitivity to rifampicin, although cases with resistance and intermediate categories were still found. Variations in positive EPTB specimens included biopsy tissue, pleural fluid, feces, gastric lavage, abscess pus, and ultraascites fluid, reflecting the spectrum of extrapulmonary TB infection. The conclusion of this study shows that rifampicin sensitivity in EPTB cases in Cilacap Regency is still dominant, indicating that the effectiveness of the first-line anti-TB regimen is still maintained, but vigilance against the potential for drug-resistant TB is still needed through continuous TCM examination.